Strengthening Regulations In Protecting Indonesian Migrant Workers Before Departing to the Destination Country - Rifqon Khairazi (Faculty of law Udayana University, 2021)
The lack of employment opportunities and intense level of job competitiveness contribute to the increasing number of job seekers in Indonesia. By the availability of opportunities to work abroad, people choose to work as migrant workers. Fact reveals many legal problems faced by migrant workers, especially those who work as domestic workers in foreign countries. This study analyzes the reasons and legal issues that cause Indonesian migrant workers to experience many violations of their rights, particularly in the pre-departure period. It discusses the rights and protection for migrant workers as stipulated in relevant laws and regulations. This research applies a normative legal method, analyzing legal documents in statutory regulations and several supporting references related to migrant workers. The results revealed that the violations of Indonesian Migrant workers’ rights occurred due to the lack of implementation of before working (pre-departure) protection. Besides, numerous migrant workers departed without going through a departure mechanism as determined in Law No. 18 of 2017 concerning the Protection of Indonesian Migrant Workers. Therefore, it is necessary to consider revising the current laws and regulations or strengthening them through implementing regulations.